Magnetism and orbitally driven spin-singlet states in Ru oxides: a muon-spin rotation study - Blundell, S; Lancaster, T; Baker, P; Hayes, W; Pratt, F; Atake, T; Rana, D; Malik, S (American Physical Society, 2008)
We have used zero-field muon-spin rotation to study the local magnetic properties of SrRuO3, Y2Ru2O7, and La2RuO5. While SrRuO3 and Y2Ru2)7 give rise to coherent precession signals, in La2Ru)5 we find no signature of long range magnetic order below the structural transition, but observe two precession signals with different temperature dependence, consistent with the nature of the noncollinear ordering being temperature dependent.